Aqueous Extract of Paeonia lactiflora and Paeoniflorin as Aggregation Reducers Targeting Chaperones in Cell Models of Spinocerebellar Ataxia 3. (25th February 2013) - Chang, Kuo-Hsuan; Chen, Wan-Ling; Lee, Li-Ching; Lin, Chih-Hsin; Kung, Pin-Jui; Lin, Te-Hsien; Wu, Yi-Ci; Wu, Yih-Ru; Chen, Yi-Chun; Lee-Chen, Guey-Jen; Chen, Chiung-Mei
Abstract : Spinocerebellar ataxia (SCA) types 1, 2, 3, 6, 7, and 17 as well as Huntington's disease are a group of neurodegenerative disorders caused by expanded CAG repeats encoding a long polyglutamine (polyQ) tract in the respective proteins. Evidence has shown that the accumulation of intranuclear and cytoplasmic misfolded polyQ proteins leads to apoptosis and cell death. Thus suppression of aggregate formation is expected to inhibit a wide range of downstream pathogenic events in polyQ diseases. In this study, we established a high-throughput aggregation screening system using 293 ATXN3/Q75 -GFP cells and applied this system to test the aqueous extract of Paeonia lactiflora ( P. lactiflora ) and its constituents. We found that the aggregation can be significantly prohibited by P. lactiflora and its active compound paeoniflorin. Meanwhile, P. lactiflora and paeoniflorin upregulated HSF1 and HSP70 chaperones in the same cell models. Both of them further reduced the aggregation in neuronal differentiated SH-SY5Y ATXN3/Q75 -GFP cells. Our results demonstrate how P. lactiflora and paeoniflorin are likely to work on polyQ-aggregation reduction and provide insight into the possible working mechanism of P. lactiflora in SCA3. We anticipate our paper to be a starting point for screening more potential herbs for the treatment of SCA3 and other polyQ diseases.